Scombroid syndrome: it seems to be fish allergy but... it isn't. Issue 5 (October 2016) - Ridolo, Erminia; Martignago, Irene; Senna, Gianenrico; Ricci, Giorgio
Abstract : Purpose of review: Scombroid poisoning is a frequent cause of admission in emergency department. In everyday clinical practice, it can be difficult to discriminate between scombroid syndrome and fish allergy. The aim of this review is to provide the clinician some instruments to make a correct differential diagnosis. Recent findings: In the last few years, a better characterization of scombroid syndrome occurred, in particular regarding its possible severe presentations. Two cases of Kounis syndrome secondary to scombroid syndrome have been described and in these cases a differential diagnosis in patients with this clinical presentation can be even more difficult. Finally, in term of diagnosis, the useful role of serum tryptase was recently consolidated. Summary: Scombroid syndrome is a histamine-induced reaction because of the ingestion of histamine-contaminated fish, whereas fish allergy is an IgE-mediated reaction. Clinical presentation can be similar and for this reason scombroid syndrome is often misdiagnosed. The differences lie in pathogenic mechanisms, possible outcome, therapy, and prevention measures. Moreover, some laboratory tests are helpful to discriminate between the two diseases.